Cloxacillin and Sodium Fusidate in Management of Shunt Infections - Rao, R. (1972)
The effectiveness of two oral antibiotics, cloxacillin and sodium fusidate, has been evaluated in the treatment of shunt infections among 37 patients allocated at random to two treatment groups. Both proved to be safe bactericidal agents giving adequate serum M.I.C. when taken by mouth. Treatment should always be started on the basis of the clinical presentation without waiting for the bacteriologist's report. The commonest infecting organism is Staphylococcus aureus. Nine shunts were lost in this study, eight through Staphylococcus aureus infection. The nasal carrier state is of considerable importance in perpetuating these shunt infections.